The IMF Debt Sustainability Analysis: Issues and Problems - Guzman, Martin Maximiliano (2015)
The Journal of Globalization and Development (JGD) sets the agenda for the future of studies in the rapidly evolving fields related to development and globalization. The journal brings together academic research and policy analysis on globalization, development, and in particular the complex interactions between them, to stimulate a creative dialogue between theory and practice, incorporating views from academics and practitioners in a variety of disciplines. Spanning the full range of perspectives on all aspects of development and globalization, and publishing the best work from scholars in developing and developed countries, the JGD represents and builds upon the most pressing debates that scholars, policymakers, and practitioners need to know about in the arena of globalization and development.